Spatial distribution and health risk assessment of potentially toxic elements along GT road from Sialkot to Rawalpindi - Ufra Naseer; Atif Ahmad; Muhammad Adnan; Muhammad Yousaf; Zhengping Du; Chuntian Qiu; Tianxiang Yue (Environmental Advances)
The rapid development and urbanization along the GT roadside has brought severe potentially toxic elements (PTEs) contamination to the soil and may lead to considerable risk to the ecosystem. In this study, the concentrations, spatial distribution along with ecological risk, and health risk assessments of PTEs (Pb, Cr, Cu, and Cd) in the GT roadside soil from Sialkot to Rawalpindi are evaluated, aiming to provide a theoretical understanding of managing and mitigating the PTEs contamination. 200 samples are collected at varying distances from the road's edge across 4 different zones (Sialkot, Gujrat, Jhelum, and Rawalpindi). A non-linear fitting model is applied to analyze the correlation between PTEs and roadside distance and shows PTEs concentration decrease with an increase in the road proximity. As distance from the road increases, ERI decreases with the highest risk at 0 m (265.99) and the lowest risk at 100 m (59.46), highlighting the gradual dissipation of the pollutant. The maximum concentration of PTEs is observed in Sialkot, while the minimum is noted in Jhelum. The mean concentrations of PTEs at 0 m were 34.9, 14.3, 27.1 and 0.66 for Pb, Cu, Cr and Cd, respectively in this descending order: Pb > Cu > Cr > Cd. The mean concentration of ERI of PTEs was 120.84 at Sialkot, 86.61 at Gujrat, 50.03 at Jhelum, and 69.63 at Rawalpindi. Cr and Cu pose a lower ecological risk as compared to Pb and Cd. Roadside soil ranges from “unpolluted” to “moderately polluted” for all metals excluding Cr. Nemerow Integrated Pollution Index (NIPI) value of 1.005 indicates that the contamination level slightly exceeds the acceptable limit. The trend of the average daily dose of PTEs (ADD) in soil via the three pathways is noted in the order of ADDinh ˂ ADDderm ˂ ADDing. Among ADD of soil, ADDderm has maximum value in adults, while ADDing and ADDinh values are maximum for children. The hazard index (HI) for all inspected PTEs in the soil is below 1, demonstrating no considerable health risk for either children or adults. The Pakistani government should prioritize traffic, and industrial-related environmental issues along GT road. This study is helpful to further analyze and assess the health risks associated with exposure to PTEs near highways, including those in industrial areas globally.